2022
DOI: 10.1186/s11658-021-00304-6
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HCG18 promotes osteosarcoma growth by enhanced aerobic glycolysis via the miR-365a-3p/PGK1 axis

Abstract: Background Osteosarcoma (OS) is a common primary bone malignancy. Long noncoding RNA HCG18 is known to play an important role in a variety of cancers. However, its role in OS and relevant molecular mechanisms are unclear. Methods Real-time quantitative PCR was performed to determine the expression of target genes. Function experiments showed the effects of HCG18 and miR-365a-3p on OS cell growth. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 54 publications
(50 reference statements)
0
19
0
Order By: Relevance
“…As to osteosarcoma, there are many published articles demonstrating that lncRNAs participate in the development of OS by regulating cell proliferation, migration, metastasis, apoptosis and chemoresistance [ 6 , 7 , 18 , 31 , 32 ]. For instance, LncRNA MALAT1 promotes tumor angiogenesis by regulating microRNA-150-5p/VEGFA signaling in osteosarcoma [ 33 ]; LncRNA SNHG16 promotes epithelial-mesenchymal transition by upregulating ITGA6 through miR-488 inhibition in osteosarcoma [ 34 ]; LncRNA HCG18 promotes osteosarcoma growth by enhanced aerobic glycolysis via the miR-365a-3p/PGK1 axis [ 35 ] and so on.…”
Section: Disscussionmentioning
confidence: 99%
“…As to osteosarcoma, there are many published articles demonstrating that lncRNAs participate in the development of OS by regulating cell proliferation, migration, metastasis, apoptosis and chemoresistance [ 6 , 7 , 18 , 31 , 32 ]. For instance, LncRNA MALAT1 promotes tumor angiogenesis by regulating microRNA-150-5p/VEGFA signaling in osteosarcoma [ 33 ]; LncRNA SNHG16 promotes epithelial-mesenchymal transition by upregulating ITGA6 through miR-488 inhibition in osteosarcoma [ 34 ]; LncRNA HCG18 promotes osteosarcoma growth by enhanced aerobic glycolysis via the miR-365a-3p/PGK1 axis [ 35 ] and so on.…”
Section: Disscussionmentioning
confidence: 99%
“…There is a growing interest in how HCG18 regulates the biological processes of cancers[ 21 ]. In the previous studies, as the most canonical and most reported regulatory pattern of lncRNA [ 22 , 23 ], HCG18 could interact with certain miRNAs to facilitate the progression in solid tumors [ 24 , 25 ]. It was confirmed that silencing of HCG18 could inhibit gastric cancer progression via obstructing the activation of PI3K/Akt signaling[ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Osteosarcoma or osteogenic sarcoma, Ewing tumors, and chondrosarcoma are the most common types of preliminary bone tumors [2]. The worldwide incidence of OS, known as the most prevalent principal malignant tumor of bone, has been reported to be about one to three cases per million per year [3,4]. Based on age, the diagram of OS occurrence is presented as a bimodal distribution curve in which two distinct peaks are recognizable; the first peak can be seen in children and adolescents, while the second peak emerges in people over the age of 50 years [5].…”
Section: Introductionmentioning
confidence: 99%